Effect of nematode control techniques on the growth and yield of plantain (MUSA SPP., AAB GROUP) - Brentu, Francis Collison (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Philosophy in Crop Protection (Nematology),